Research of systemic immunity and hemostasis in women with pathological processes of the epithelium of the genitals with atypia of cells of unclear genesis in women with infertility - В. В. Камінський; О. Я. Бондарук; І. О. Гак (Publishing House TRILIST, 2020)
Purpose of the study: to study the systemic immunity and hemostasis in women with infertility and pathological processes of glandular epithelium of genitals with atypical glandular cells not otherwise specified. Materials and methods. The study included 173 women with infertility and pathological processes of glandular epithelium of genitals with atypical glandular cells not otherwise specified (main group). The comparison group consisted of 100 women with infertility and without pathological processes of cervical epithelium. All patients underwent studies of the immune systems (population of lymphocytes, circulating immune complexes) and hemostasis (screening coagulation tests, number and aggregation function of platelets). Results. Analysis of the immune system revealed certain changes in the main group, more pronounced in women with endometrial pathology - inhibition of the cell link (evidenced by a decrease in absolute and relative CD3+ T cells value, absolute number of CD4+, CD16 and phagocytic number) against the background of humoral immunity activation (increase in the CD22+ level, circulating immune complexes, IgG and IgA). The study of the vascular-platelet hemostasis showed a decrease of platelets against the background of a tendency to an increase in platelet anisocytosis and an increase in platelet counts in women with endometrial pathology. An analysis of platelet aggregation function revealed a significant increase in platelet aggregation to adenosine diphosphate, adrenaline and collagen in patients with endometrial pathology, also a tendency to hypercoagulation. Conclusions. In women with infertility and pathological processes of glandular epithelium of genitals with atypical glandular cells there is suppression of the cellular immune system against the background of humoral immunity hyperactivation. Activation of the vascular-platelet hemostasis and a tendency to hypercoagulative state were revealed.